Bacterially Induced Mineralization of Calcium Carbonate in Terrestrial Environments: The Role of Exopolysaccharides and Amino Acids - Braissant, Olivier; Cailleau, Guillaume; Dupraz, Christophe; Verrecchia, Eric (My University, 2003)
This study stresses the role of specific bacterial outer structures (such as glycocalix and parietal polymers) on calcium carbonate crystallization in terrestrial environments. The aim is to compare calcium carbonate crystals obtained in bacterial cultures with those obtained during abiotically mediated synthesis to show implications of exopolysaccharides and amino acids in the mineralogy and morphology of calcium carbonate crystals produced by living bacteria. This is done using various amounts of purified exopolysaccharide (xanthan EPS) and L-amino acids with a range of acidities. Amino acids and increasing xanthan content enhance sphere formation in calcite and vaterite. Regarding calcite, the morphology of crystals evolves from rhombohedral to needle shape. This evolution is characterized by stretching along the c axis as the amino acid changes from glutamine to aspartic acid and as the medium is progressively enriched in EPS. Regarding vaterite, the spherulitic habit is preserved throughout the morphological sequence and starts with spheres formed by the agglomeration of short needles, which are produced in a xanthan-free medium with glutamine. Monocrystals forming spheres increase in size as xanthan is added and the acidity of amino acids (glutamic and aspartic acids) is increased. At high xanthan concentrations, amino acids, and mainly aspartic and glutamic acids, induce vaterite precipitation. The role of the carboxyl group is also probably critical because bacterial outer structures associated with peptidoglycan commonly contain carboxyl groups. This role, combined with the results presented here, clearly demonstrate the influence of bacterial outer structure composition on the morphology and mineralogy of bacterially induced calcium carbonate. This point should not be neglected in the interpretation of calcite cements and carbonate accumulations in terrestrial environments.